Mesenchymal Stem Cell-Macrophage Crosstalk and Maintenance of Inflammatory Microenvironment Homeostasis - Lu, Di; Xu, Yan; Liu, Qiuli; Zhang, Qi (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSCs) exhibit potent immunoregulatory abilities by interacting with cells, particularly macrophages, of the adaptive and innate immune system. Many immune disorders, including inflammatory bowel disease (IBD), acute lung injury or wound healing etc., have been reported to involve the imbalance of M1/M2 macrophage. The present review we summarized how MSC and macrophage interact, communicate, and exchange information through different ways such as cell-to-cell contact, secretion of soluble factors, and organelle transfer. Moreover, we discuss the consequences of this dynamic dialogue between MSC and macrophage described by their phenotypic and functional plasticity, and how MSC-macrophage crosstalk to affect the development of the disease?